Pulse generation using avalanche transistor for ultra wide band communication: Analysis and simulation results - Shahid, Zeeshan; Khan, Sheroz; Alam, A. H. M. Zahirul (2012)
In this paper a simple pico-second pulse generator, its working principle and design. The design is supported by relevant theory, explaining the function of the circuit, and to ultimately show how the resulting pulses are related in their widths to respective parameter values of the circuit elements. The circuit is based on using four timers ICs with transistor and other external logic component. The resulting pulse is studied for its pulse width, amplitude and with a power spectral density lying well within the FCC defined range. The preliminary simulation results of this work shows a generated pulse with a width of around of 180 picoseconds, even shorter than reported in recently reported works.